Re-Imagining the Business Trust as a Sustainable Business Form - Lee-Ford Tritt; Ryan Scott Teschner (Washington University Law Review, 2019)
An important policy debate has emerged in the United States concerning how business should evolve to encapsulate more fully the burgeoning sustainability-conscious management paradigm. At issue in this debate is the proper role of business in society. The modern trend in business is to consider more than just shareholder profits. In the United States, companies are increasingly incorporating sustainability practices into their business models. However, by practice and by law, the traditional corporate management paradigm—the shareholder primacy model—holds that the singular social responsibility of business is to maximize shareholder interests, principally shareholder profits. This model conflicts with the sustainability management paradigm, which reflects the view that business should maximize value for society. Some states have realized the shortcomings of the traditional corporate management model and have enacted constituency statutes or created new corporate forms to account for the growth in sustainable corporate practices. However, these statutes and corporate forms have their own shortcomings. Historically, business trusts have been used to circumvent overly-restrictive corporate organizational and legal limitations. Entrepreneurs should once again look to this business form to pursue sustainable practices while maintaining profitability. Due to business trusts’ structure and flexibility, they are an ideal vehicle for sustainable businesses. Accordingly, by drawing upon trust law and corporate law, this Article articulates an interdisciplinary, systematic application of business trusts as an alternative organizational form to corporations for the socially-conscious business management construct.
Keywords: Shareholder primacy; Business trust; Corporate governance; Sustainability; Corporate management; Corporate law; Trust law